The Association between Demographic Factors and Health Literacy AmongPost-Treatment Recovery of Pulmonary Tuberculosis Patients - Qomariyah, Farida Nur (Journal of Nursing Periodic, 2024)
Introduction: Health literacy on successful pulmonary tuberculosis treatment is a intricate problem influenced by factors such as demographic factors. This research aimed to analyze the association between demographic factors and health literacy among post-treatment recovery of pulmonary tuberculosis patients.Methods: This retrospective study analyzed the association between demographic factors and health literacy levels of 128 among post-recovery treatment of pulmonary tuberculosis patients in four primary health care settings in Jember Regency from October-November 2022. The inclusion criteria in this research were as follows: 1) must be older or equal to 18 years of age, 2) declared cured of tuberculosis in the of the treatment in 2021, 3) Indonesia citizens, and 4) able to speak, write and read the Indonesia language. This study used demographic questionnaire and health literacy questionnaire for data collection. The chi-square test was used to analyze all of the variables with significance level of 95%(α = 0.05). Results: This research found that the demographic factors that had an association with health literacy level were age (p=0.04), educational level (p<0.01), income (p<0.01), and living area (p<0.01). While,the demographic factors that were unassociated with health literacy level were gender (p=0.67),occupation (p=0.33) and marital status (p=0.41). Conclusions: To make the TB medication program more successful, healthcare providers and the government should pay attention to demographic characteristics that influence health literacy and drug adherence.